Description and Functional Outcomes of a Novel Interdisciplinary Rehabilitation Program for Hospitalized Patients With COVID-19. (December 2021) - Patel, Nija; Steinberg, Chelsea; Patel, Ruchi; Chomali, Cheryl; Doulatani, Gargi; Lindsay, Leroy; Jaywant, Abhishek
Abstract : Objectives: The aims of the study were to describe an interdisciplinary inpatient rehabilitation program for patients recovering from COVID-19 and to evaluate functional outcomes. Design: This is an analysis of retrospective data captured from the electronic health record of COVID-19 patients admitted to the rehabilitation unit ( N = 106). Rehabilitation approaches are described narratively. Functional gain was evaluated using the Activity Measure for Postacute Care 6 Clicks, basic mobility and daily activities. Results: Interdisciplinary approaches were implemented to address the medical, physical, communication, cognitive, and psychosocial needs of COVID-19 patients. COVID-19 patients exhibited significant improvements in basic mobility (Activity Measure for Postacute Care for basic mobility, P < 0.001, Cohen d = 1.35) and daily activities (Activity Measure for Postacute Care for daily activities, P < 0.001, Cohen d = 1.06) from admission to discharge. There was an increase in ambulatory distance as well as the percentage of the patients who were able to breathe on room air. At discharge, fewer patients required supplemental oxygen on exertion. Eighty percent of the patients were discharged home after an average length of stay of 17 days. Greater functional improvement was associated with younger age, longer intubation duration, and participation in psychotherapy, but not a history of delirium during hospitalization. Conclusions: Early rehabilitation is associated with improved mobility and independence in activities of daily living after COVID-19. Abstract : Supplemental digital content is available in the text.